1982
DOI: 10.1159/000123360
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Evidence for Endogenous Substance-P-Like Immunoreactivity in the Rat Pituitary Gland

Abstract: Substance P (SP) is known to act on pituitary hormone release either at the hypothalamic level or directly at the pituitary level. In order to investigate whether SP is present in the pituitary gland and to localize the peptide at the cellular and subcellular levels, the immunocytological method was used. Rat pituitaries were fixed and frozen. Ultrathin sections, obtained by cryoultramicrotomy, were incubated with anti-SP serum. The antigen-antibody reaction was detected by 4-chloro-1-naphtol. SP immunoreactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(36 citation statements)
references
References 15 publications
2
34
0
Order By: Relevance
“…However, SP has also been detected by immunocytochemistry within thyrotrophs, lactotrophs and somatotrophs of the rat anterior pituitary (8,9) as well as within a subset of thyrotrophs in the human pituitary (10). The presence of preprotachykinin A mRNA in the anterior pituitary gland (11) suggests that SP is synthesized in the gland.…”
Section: Introductionmentioning
confidence: 99%
“…However, SP has also been detected by immunocytochemistry within thyrotrophs, lactotrophs and somatotrophs of the rat anterior pituitary (8,9) as well as within a subset of thyrotrophs in the human pituitary (10). The presence of preprotachykinin A mRNA in the anterior pituitary gland (11) suggests that SP is synthesized in the gland.…”
Section: Introductionmentioning
confidence: 99%
“…Another is that the moderate number of SP-immunoreactive nerve fibers present within the anterior pituitary lobe itself could have a direct action on the endocrine cells ( Ju and Liu, 1989;Muelsen et al, 1989). Finally, it may be that SP produced within anterior pituitary cells influences part of the cells via a paracrine mode of action (Jonassen et al, 1987;Aronin et al, 1986;DePalatis et al, 1982;Morel et al, 1982). Yet to be investigated is whether SP exerts its actions on PIU and LH-containing anterior pituitary cells directly via surfacelocalized receptors.…”
Section: Introductionmentioning
confidence: 99%
“…This undecapeptide was isolated from the hypothalamus and characterized by Leeman in 1970-1971 (2, 3). Immunocytochemical studies have demonstrated an SP-containing neuronal system in the hypothalamus (4)(5)(6)(7)(8)(9)(10), and the peptide has been localized to cells of the anterior pituitary gland as well (11,12). In addition, SP receptors have been localized to various regions of the hypothalamus and pituitary (5,6 (R-11) has been fully characterized (11) and is directed at the carboxyl terminus.…”
Section: Introductionmentioning
confidence: 99%
“…This undecapeptide was isolated from the hypothalamus and characterized by Leeman in 1970-1971 (2, 3). Immunocytochemical studies have demonstrated an SP-containing neuronal system in the hypothalamus (4-10), and the peptide has been localized to cells of the anterior pituitary gland as well (11,12 In Vivo Experiments. Experiment I.…”
mentioning
confidence: 99%